Selective-area lateral epitaxial overgrowth of SiC by controlling the supersaturation in sublimation growth. Issue 12 (1st March 2018) - Yang, Xianglong; Chen, Xiufang; Peng, Yan; Hu, Xiaobo; Xu, Xiangang
Abstract : We realized the selective-area lateral epitaxial overgrowth of SiC on a 6H-SiC (0001) seed crystal by controlling the supersaturation in sublimation growth. Abstract : We realized the selective-area lateral epitaxial overgrowth of SiC on a 6H-SiC (0001) seed crystal by controlling the supersaturation in sublimation growth. For crystal growth from the vapor phase, the nucleation and growth rate of SiC crystals are critically dependent on supersaturation. Non-uniformity of the supersaturation over the 6H-SiC seed surface was effectively controlled by modulating the thermal profile through forming a predefined pattern of different thermal conductivity distributions on the backside of the seed. Localized nucleation and growth due to high supersaturation started at the lower temperature regions corresponding to higher thermal conductivity on the backside of the seed, subsequently followed by the lateral growth of 6H-SiC from the sidewalls of the preferential growth regions to the higher temperature regions corresponding to lower thermal conductivity. It was found that the piling up of dislocation etch pits repeats the arrangement and boundaries of the predefined pattern, and the free lateral growth was accompanied by a sharp decrease in the density of threading dislocation. This may be a promising technique for obtaining high-quality SiC crystals with low threading dislocation density.